Cash Waqf Literacy in Indonesia and Malaysia: An Analysis of Journal Publications and Trends (2018-2023) - Syibly, M. Roem (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This research aims to determine waqf literacy products in journals in Indonesia and Malaysia, especially cash waqf, which is expected to address the problem of low public understanding of cash waqf and may be due to not being supported by adequate literacy products. Research on waqf literacy products that focus on cash waqf is more due to the increasing trend of cash waqf, along with its great potential. The research method uses bibliometric mapping with metadata obtained from the Publish or Perish (PoP) application to access Google Scholar by filtering the titles Cash Waqf Indonesia and Malaysia and its publications in the form of journals. To visualize the bibliometric network, this study used the VOSViewer version 1.6.19. The accessed journals are limited to the last five years, 2018-2023. From the search results, Cash Waqf Indonesia had 106 journal articles, and Cash Waqf Malaysia had 40. Indonesian and Malaysian cash waqf literacy products published in journals are few. Likewise, cash waqf studies associated with productive waqf themes are still few in number, and the focus of productive waqf studies is still limited to sukuk and micro-enterprises. The low level of public understanding of cash waqfs in Indonesia and Malaysia may be partly due to the lack of literacy products.